First‐Price Split‐Award Auctions in Procurement Markets with Economies of Scale: An Experimental Study. Issue 3 (14th October 2018) - Kokott, Gian‐Marco; Bichler, Martin; Paulsen, Per
Abstract : We experimentally study first‐price split‐award auction formats as they can be found in procurement markets where suppliers have economies of scale. Our analysis includes sequential and combinatorial auctions, which allow for bids on the package of two shares and single shares. We derive equilibrium predictions as hypotheses for bidder behavior in our laboratory experiments. These equilibrium predictions help explain important patterns in our experimental results. The combinatorial first‐price sealed‐bid auction yields lower prices than the other mechanisms and is highly efficient independent of the extent of scale economies. With strong economies of scale both combinatorial auction formats let the auctioneer incur significantly lower procurement costs and generate high efficiency compared to the sequential auction. We also find high efficiency of the combinatorial first‐price sealed‐bid auction in experiments with diseconomies of scale, making these auctions attractive if the buyer has uncertainty about the economies of scale in a market. Our analysis shows that combinatorial split‐award auctions can be an attractive alternative for the buyer compared to their sequential counterparts.